Sunburn and sun protection during recreational outdoor sport in summer: findings from the German general population aged 16-65 years - Görig, Tatiana (2024)
Background: Sunburn can increase one's risk of developing skin cancer. We aimed to quantify the prevalence of sunburn during recreational outdoor sport (ROS) in summer, to explore the use of different sun protection measures, and to examine factors associated with sunburn during ROS using a population-based sample from Germany. Methods: For this cross-sectional study, 2081 individuals aged 16–65 years who reported being engaged in ROS in summer were surveyed via standardized telephone interviews in 2020 (National Cancer Aid Monitoring, NCAM). Results: Overall, 16.7% reported experiencing at least one sunburn during ROS in the past twelve months. Sunburn occurrence was negatively associated with the age of the participants (e.g. OR = 0.49 in 56–65 year-olds, p <.001), and positively associated with skin type I/II (OR = 1.55, p <.001) and with having a higher number of nevi (OR = 1.42, p =.005). While wearing sleeved shirts was the most frequently-used sun protection measure during ROS (74.9%), wearing headgear was least common in our sample (29.0%). In multivariate analyses, sunburn was positively associated with the use of sun protection measures (e.g. OR = 1.32 for wearing sleeved shirts, p =.02). Conclusions: Our nationwide data show that ROS is one of the settings where sun protection should play a greater role. Especially in organized sports, particular attention should be devoted to organizational (e.g. exercise outside peak hours) or contextual measures (e.g. shade by the natural or built environment) to prevent skin cancer in later life.